Intergenerational Transmission of Self-Employed Status in the Informal Sector : A Constrained Choice or Better Income Prospects? Evidence from Seven West-African Countries - Pasquier-Doumer, Laure (World Bank, Washington, DC, 2017)
Social reproduction is the highest for self-employed as shown by an extensive literature from developed and developing countries. Very few studies however document the reason for this high intergenerational correlation of the self-employed status. The purpose of this paper is to test if the second-generation of self-employed has an advantage related to the first-generation in the African context. It aims at highlighting the debate on firms heterogeneity in the informal sector, by identifying factors of informal business success. In addition, this paper seeks to contribute to understand the intergenerational transmission of inequalities. Using 1-2-3 surveys collected in the commercial capitals of seven West African countries in 2001-2002, this paper shows that the second-generation of informal self-employed does not have better outcomes than the first one, except when they choose a familial tradition in the same sector of activity. Thus, in the African context, having a self-employed father does not provide any advantage in terms of profit or sales and is not sufficient for the transmission of valuable skills. On the other hand, informal entrepreneurs who have chosen a specific enterprise based on familial tradition have a competitive advantage. Their competitive advantage is partly explained by the transmission of enterprise-specific human capital, acquired through experiences in the same type of activity and by the transmission of social capital that guarantees a better clientele and a reputation.